(untitled) (Ameghiniana, 2013)
Resumen. Se describen diez especies del morfogénero de Pteridophylla Taeniopteris: T. anavolans Anderson y Anderson, T. densinervis Menéndez, T. homerifolius Anderson y Anderson, T. magnifolia Rogers, T. plicatella (Solms) Menéndez, T. thomsoniana (Arber) Blaschke y Grant-Mackie, T. vittata Brongniart, T. wianamattae (Feistmantel) Walkom, Taeniopteris sp. A, Taeniopteris sp. B y dos nuevas especies T. lutzae Gnaedinger y Herbst y T. troncosoi Gnaedinger y Herbst. Proceden de tres áreas del norte de Chile (entre los 27° y 33° S): cerro La Ternera (Formación La Ternera), Vicuña (Formación Las Breas) y Los Molles (Formación El Puquén), todas del Triásico Superior. Las especies de Argentina, Chile y Sud África están principalmente distinguidas por un análisis de las venas laterales con patrón simple, dicotómico y anastomosado. Se presenta un cuadro comparativo con el patrón de venación de estas especies y otro con su distribución estratigráfica. Abstract. TRIASSIC PTERIDOPHYLLA FROM THE NORTE CHICO OF CHILE. I. THE GENUS TAENIOPTERIS BRONGNIART. Ten species of the Pteridophylla genus Taeniopteris Brongniart are described. They are T. anavolans Anderson and Anderson, T. densinervis Menéndez, T. homerifolius Anderson and Anderson, T. magnifolia Rogers, T. plicatella (Solms) Menéndez, T. thomsoniana (Arber) Blaschke and Grant-Mackie, T. vittata Brongniart, T. wianamattae (Feistmantel) Walkom, Taeniopteris sp. A, Taeniopteris sp. B and two new species: T. lutzae Gnaedinger and Herbst and T. troncosoi Gnaedinger and Herbst. They were found in three different areas of northern Chile (between 27° and 32° S): Cerro La Ternera (La Ternera Formation), Vicuña (Las Breas Formation) and Los Molles (El Puquén Formation). All these formations correspond to Upper Triassic sequences. The species of Argentina, Chile and South Africa are mainly distinguished by an analysis of the secondary venation with simple, dichotomous (or branched) and anastomosed pattern. A comparative table for these species is presented with the characterization of their venation patterns. Also a stratigraphic distribution chart of this genus for the Triassic of Argentina and Chile is given.